Penelitian Pupuk Biofertilizer Berbahan dasar Kulit Buah Nanas dan Abu Rumput Gajah dengan pengaruh Berat bahan dan Durasi fermentasi - Dian Pratiwi Tejo Kusumo; Dimas Arnanda; Kindriari Nurma Wahyusi; Dyah Suci Perwitasari; Retno Dewati (G-Tech: Jurnal Teknologi Terapan, 2025)
This research develops a biofertilizer production method using pineapple peel waste and elephant grass ash as raw materials. Pineapple peel contains nutrients that can improve soil fertility, while elephant grass, commonly used as livestock feed, has high silica content beneficial to the soil when used as fertilizer. The research aimed to produce a biofertilizer and examine the effects of material weight and fermentation duration on the levels of Nitrogen (N), Phosphorus (P), and Potassium (K), assessing whether the results meet Indonesian National Standard (SNI) fertilizer requirements. The fermentation process lasted approximately 35 days. The fermented biofertilizer was analyzed using the Micro Kjeldahl method for Nitrogen, UV-Vis Spectrophotometry for Phosphorus, and Atomic Absorption Spectrophotometry (AAS) for Potassium. The results showed the highest concentrations of Nitrogen (2.98%), Phosphorus (2.43%), and Potassium (3.39%) were obtained using 40 grams of elephant grass ash and 35 days of fermentation. The analysis indicated that increasing the amount of elephant grass ash and the fermentation duration resulted in higher N, P, and K levels. These findings align with SNI fertilizer standards, highlighting the potential of using sustainable and easily accessible materials to enhance organic fertilizer production efficiency.